HUBUNGAN PERILAKU PERAWAT DALAM PENERAPAN INTERNATIONAL PATIENT SAFETY GOALS 5 (IPSG 5) DENGAN KEJADIAN PHLEBITIS - Riski " Ismawati; Sofiana " Nurchayati; Febriana " Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   Patient safety is a system that prevents the occurence of undesirable events (KTD). One of the undesirable events in hospital is phlebitis caused by infusion. The purpose of this research is to identify the relationship between application international patient safety goals 5 (IPSG 5) with the  incidence of phlebitis in hospital. This research is descriptive study with prospective approach. The samples were taken from the nursing ward III and patients with infusion in ward III room of Arifin Achmad Hospital  Riau Province with 91 respondents. The sampling technique is total sampling. The data is collected by questionnaire that already tested for validity by the value of r count ranging from 0.513 up to 0.830 and 0.943 reliability with r results as well as the installation documentation of infusion therapy. The data is analyzed  by univariate and  bivariate with Chi- square test. The results show p value was 0,00 (α < 0,05), that there is significantly relationship between nurse behavior  of application international patient safety goals 5 (IPSG 5) with incidence of phlebitis.  It is suggested that nurse need to make a documentation note of  infusion and observe the infusion to minimize the occurrence of phlebitis. Keyword: IPSG 5, Patient Safety, Phlebitis